Multi-system inflammatory syndrome presenting with refractory shock in an infant, temporally associated with SARS-CoV2 infection - Devadas, Sahana; Ganesh, Shruthi; Govindarajan, Varun (International Journal of Contemporary Pediatrics, 2021)
Children with COVID-19 largely remain asymptomatic or mildly symptomatic with gastroenteritis or influenza like presentation. However, few of them go on to develop features of multi-system inflammatory syndrome secondary to dysregulated cytokine release, resulting even in death. We report a 45 days old infant who presented to us with fluid unresponsive shock following protracted vomiting few hours prior to arrival. Eight days prior, child was admitted in COVID Isolation centre with mild illness, after testing positive on rapid Antigen Test and discharged 3 days later. Child when brought was severely acidotic and hence electively intubated. Shock did not improve even following multiple boluses and inotropic support on mechanical ventilation. Encephalopathy, myocardial dysfunction and acute kidney injury, with elevated inflammatory markers post COVID-19 suggested multi-system inflammation syndrome in him. The infant deteriorated rapidly and succumbed even before targeted therapy could be initiated. MIS-C presenting with refractory shock is increasingly being reported in pediatric age group and these children rapidly deteriorate without early recognition and treatment. Clinicians need a heightened suspicion for cytokine storm related complications and institute early immune-modulative therapy, especially during the present COVID-19 pandemic.